2013
DOI: 10.1155/2013/541079
|View full text |Cite
|
Sign up to set email alerts
|

Strong Convergence Theorems for Solutions of Equations of Hammerstein Type

Abstract: We consider an auxiliary operator, defined in a real Hilbert space in terms of and , that is, monotone and Lipschitz mappings (resp., monotone and bounded mappings). We use an explicit iterative process that converges strongly to a solution of equation of Hammerstein type. Furthermore, our results improve related results in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is known that (J E +t 0 F ) and (J E * +t 0 K) are bijections (see e.g, Chuang [17]). It can be easily verified that if E is a smooth, strictly convex and reflexive Banach space and F : E → E * is a monotone mapping with R(J E + tF ) = E * , then for each t > 0, the resolvent J E t of F defined by…”
Section: Resultsmentioning
confidence: 99%
“…It is known that (J E +t 0 F ) and (J E * +t 0 K) are bijections (see e.g, Chuang [17]). It can be easily verified that if E is a smooth, strictly convex and reflexive Banach space and F : E → E * is a monotone mapping with R(J E + tF ) = E * , then for each t > 0, the resolvent J E t of F defined by…”
Section: Resultsmentioning
confidence: 99%
“…Mustafa Nader gave conditions that ensure the existence and the uniqueness of the solution for equation (1) in the space [4]. Authors in [5][6][7][8] found sequences converged to the exact solution of equation 1under such assumptions.…”
Section: Introductionmentioning
confidence: 99%